ÐšÑ€Ð¸Ð¾ÐºÐ¾Ð½ÑÐµÑ€Ð²Ð¸Ñ€Ð¾Ð²Ð°Ð½Ð¸Ðµ Ñ€ÐµÐ¿Ñ€Ð¾Ð´ÑƒÐºÑ‚Ð¸Ð²Ð½Ñ‹Ñ… Ð¿Ñ€Ð¾Ð´ÑƒÐºÑ‚Ð¾Ð² Ð½Ð°ÑÐµÐºÐ¾Ð¼Ñ‹Ñ… - Relina, Liana I.; Gulevsky, Aleksandr K. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2013)
The review describes the basic problems of cryopreservation of insect germplasm as well as approaches to their solution, which have been developed to date. The peculiarities of cryopreservation procedures for insect embryos and sperm are discussed in comparison with cryopreservation methods for reproductive products of other species. A brief description of species, for which the cryopreservation protocols are considered, substantiates the need for long-term storage of their genetic material. In the review we categorized the insect species, for which the designed low-temperature storage techniques are presented, in systematic taxa (orders). The prospects for the further development in this area are discussed.